Optimizing Student Motivation and Learning Outcomes Through Group Investigation Cooperative Learning Model on Ratio Material: A Study of Mathematical Reasoning Ability - Anggriyani, Meli; Syaharuddin, Syaharuddin; Mandailina, Vera; Abdillah, Abdillah; Raza, Wasim (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the effectiveness of the application of the Group Investigation cooperative learning model in optimizing student motivation and learning outcomes on ratio material, as well as analyzing its contribution to mathematical reasoning skills. This study used a quantitative approach with a pre-test and post-test design involving 20 junior high school students in grade VII. Data were obtained through mathematical reasoning ability test, motivation questionnaire, and analysis of students' learning outcomes. The results showed an increase in the mean score from pre-test to post-test by -6.50 (p = 0.001) which reflects more uniform student learning outcomes. Regression analysis showed a very strong relationship between the independent variable (mathematical reasoning) and the dependent variable (motivation and learning outcomes) with an R value of 0.929 and R2 of 86.4%, indicating that motivation and learning outcomes explained most of the variation in reasoning ability. Specifically, the contribution of mathematical reasoning (X) to student learning outcomes (Y2) was 38.94% while the contribution of motivation (Y1) to mathematical reasoning reached 45.83%. In addition, regression analysis shows that motivation has a significant influence on mathematical reasoning ability, while learning outcomes have a positive but statistically insignificant influence. This finding indicates that the Group Investigation cooperative learning model is not only effective in improving student learning outcomes, but also has an important role in strengthening mathematical reasoning skills through increased motivation. Therefore, cooperative learning strategies that emphasize increased motivation need to be applied in mathematics learning to optimize students' analytical thinking skills.